Genetically Predicted Circulating Concentrations of Micronutrients and COVID-19 Susceptibility and Severity: A Mendelian Randomization Study - Daniel, Neil; Bouras, Emmanouil; Tsilidis, Konstantinos K.; Hughes, David J. (Frontiers in Nutrition, 2022)
Background: Coronavirus disease 2019 (COVID-19) is caused by the severe acute respiratory syndrome coronavirus 2 which since 2019 has caused over 5 million deaths to date. The pathogenicity of the virus is highly variable ranging from asymptomatic to fatal. Evidence from experimental and observational studies suggests that circulating micronutrients may affect COVID-19 outcome. Objectives: To complement and inform observational studies, we investigated associations of genetically predicted concentrations of 12 micronutrients (β-carotene, calcium, copper, folate, iron, magnesium, phosphorus, selenium, vitamin B-6, vitamin B-12, vitamin D and zinc) with SARS-CoV-2 infection risk and COVID-19 severity using Mendelian randomization (MR). Methods: Two-sample MR was conducted using 87,870 individuals of European descent with COVID-19 diagnosis and 2,210,804 controls from the COVID-19 host genetics initiative. Inverse variance-weighted MR analyses were performed with sensitivity analyses to assess the impact of potential violations of MR assumptions. Results: Compared to the general population, nominally significant associations were noted for higher genetically predicted vitamin B-6 (Odds ratio per standard deviation [ORSD]: 1.06; 95% confidence interval [CI]: 1.00, 1.13; p-value = 0.036) and lower magnesium concentrations (ORSD: 0.33; 95%CI: 0.11, 0.96; P = 0.042) with COVID-19 infection risk. However, the association for magnesium was not consistent in some sensitivity analyses, and sensitivity analyses could not be performed for vitamin B-6 as only two genetic instruments were available. Genetically predicted levels of calcium, folate, β-carotene, copper, iron, vitamin B-12, vitamin D, selenium, phosphorus or zinc were not associated with outcomes from COVID-19 disease. .Conclusions: These results, though based only on genetically predicated circulating micronutrient concentrations, provide little evidence for possible associations of micronutrients with COVID-19 outcomes.